Learning Media for Writing Fantasy Story Text Based on Scientific Plus Using Adobe Flash - Balqis, Karina; Purnomo, Mulyadi Eko; Oktarina, Santi (Jurnal Ilmiah Sekolah Dasar, 2021)
The lack of learning media that facilitates students causes students to experience difficulties in learning. In addition, teachers still have difficulty presenting material for writing fantasy story texts and teachers use learning only to provide material, not at the evaluation stage. This has an impact on students' lack of understanding. This study analyses the validity of the learning media based on the alpha test, the practicality of the learning media and the effectiveness of the learning media. This type of research is development research. The model used to develop the media is Alessi and Trolip (2001), consisting of planning, design and development stages. Data was collected through expert review, interviews, and tests. The research subjects were nine experts, which included media experts, material experts, and linguists. The product trial subjects were 32 students. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The alpha test results showed the validity of the learning media of 92.50% with a very appropriate category. Beta test results show the practicality of the product is 85.49%, with an excellent category. It can be concluded that scientific-based learning media plus using adobe flash can be applied in learning to write fantasy story texts. This research implies that teachers in learning can use the developed media.